2022
DOI: 10.47836/ifrj.29.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion analysis of carbon dioxide released by egg respiration at different storage temperatures based on FLUENT

Abstract: Temperature is an important factor affecting the changes in the amount of gas exchanged between eggs and the surrounding during storage. The effect of temperature changes on the release of carbon dioxide (CO2) from eggs was studied using eggs from the same breed. The experimental samples were divided into three groups, and placed in a storage box at 4, 25, or 35°C with 65% relative humidity for 20 days, and a breathalyser was used to measure the amount of CO2 released by the eggs. The FLUENT software was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…demonstrated that the standard k -epsilon model performed better in simulations of heavy gas diffusion, and the simulation results were validated by experimental results. The diffusion process of the gas was modeled by Fluent’s species transport model . Due to the lack of LPG-related parameters in the Fluent gas database, and the fact that LPG consists primarily of propane and butane gas as its main components, Liang et al used a mixture of 47% propane and 53% butane instead of LPG.…”
Section: Cfd Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that the standard k -epsilon model performed better in simulations of heavy gas diffusion, and the simulation results were validated by experimental results. The diffusion process of the gas was modeled by Fluent’s species transport model . Due to the lack of LPG-related parameters in the Fluent gas database, and the fact that LPG consists primarily of propane and butane gas as its main components, Liang et al used a mixture of 47% propane and 53% butane instead of LPG.…”
Section: Cfd Numerical Simulationsmentioning
confidence: 99%
“…The diffusion process of the gas was modeled by Fluent’s species transport model. 35 Due to the lack of LPG-related parameters in the Fluent gas database, and the fact that LPG consists primarily of propane and butane gas as its main components, Liang et al 36 used a mixture of 47% propane and 53% butane instead of LPG. We compared the physical characteristics (gaseous density, molecular weight, and explosion limit) and transport properties (kinematic viscosity, thermal conductivity, and diffusion coefficient) of both gases and LPG (as shown in Table 1 ), and it should be noted that the light hydrocarbon components of LPG improve its diffusion coefficient.…”
Section: Cfd Numerical Simulationsmentioning
confidence: 99%